Steam temperature and flow maldistribution in superheater headers - du Preez, Jean-Pierre (Department of Mechanical Engineering, 2020)
Heat exchangers and steam headers are at the heart of any boiler and are susceptible to a range of failures including tube leaks, ligament cracking, creep and fatigue. These common forms of header failure mechanisms can be exacerbated by local thermal stresses due to temperature and flow maldistribution at full and partial boiler load operations. The purpose of this project is to develop process models of the outlet stubbox header of a final superheater (FSH) heat exchanger in a 620MW coal-fired drum type boiler. The process models were used to assess the impact of steam flow and temperature distribution on the thermal stresses in the header material. The process models were developed using Computational Fluid Dynamics (CFD) and Finite Element Analysis (FEA). Thermocouples were installed at key locations on the stubbox headers to monitor metal temperatures and the measured metal temperatures served as boundary values and for validation of the CFD results. The thermocouple data was analysed for three different steady state boiler loads, namely full load, 80% load and 60% load. It showed that the temperature distribution across these headers was not uniform, with a maximum temperature difference across the outlet stubbox of 40℃ at full load and 43℃ at partial loads. Other relevant power plant data, such as steam pressure, was provided from the power plant's Distributed Control System (DCS) and was used as boundary conditions for the CFD models. The exact mass flow distribution across the inlet stubs of the outlet stubbox header was unknown and was estimated using a CFD model of the inlet stubbox header and steam mass flow values from power plant's DCS system. A CFD model was created for each of the three boiler loads at steady state conditions. The CFD results provided the metal temperature profile, internal steam temperature distribution and pressure distribution across the header. The CFD solid temperatures were validated using the thermocouple readings and found to be in agreement. The CFD results were exported to the FEA models, where specific displacement constraints for thermal expansion were utilised. The FEA models were used to assess the extent of thermal stresses due to thermal expansion only, as well as stresses due to thermal expansion combined with internal pressure. High local stresses were found at the borehole crotch corners of the rear outlet branch and inlet stubs. However, these are below 0.2% proof strength at elevated temperatures. The high local stresses thus did not result in local plastic deformation but contribute to exacerbate steady state failure mechanisms such as creep.